Compact UWB flexible elliptical CPW‐fed antenna with triple notch bands for wireless communications - Lakrit, Soufian; Das, Sudipta; Ghosh, Soumendu; Madhav, Boddapati Taraka Phani (International journal of RF and microwave computer-aided engineering, 2020)
A coplanar waveguide (CPW)‐fed flexible elliptical antenna with triple band notched characteristics is presented in this article. The designed antenna consists of an elliptical patch and slots incorporated CPW feed line to cover the bandwidth requirements for ultra‐wideband (UWB) applications. The designed UWB antenna has a fractional bandwidth of about 166.19% (1.20‐13 GHz) with a center frequency of 7.1 GHz in simulation and about 170.10% (1.05‐13 GHz) with a center frequency of 7.025 GHz in measurement. The overall dimension of the proposed flexible antenna is 45 × 35 × 0.6 mm3. The triple notched bands are realized by designing with circular shaped split‐ring‐resonators (SRRs) and defected ground structure (DGS). According to the measurement, first notched band (2.0−2.70 GHz) is generated for rejecting 2.4 GHz WLAN by introducing a single circular ST‐SRR on the radiating patch. The second notch (3.45‐3.80 GHz) is obtained by embedding another circular ST‐SRR on the patch to mitigate the interference of 3.5 GHz Wi‐MAX system. Finally, due to presence of DGS, third notch (5.15‐6.20 GHz) is produced which suppresses the interference from 5.5 GHz Wi‐MAX and 5.2/5.8 GHz WLAN systems. The proposed antenna offers excellent performance in different flexible conditions that confirm its applicability on curved surfaces for UWB systems.